Evaluation Methods Review of the Innovation Capacity of Companies Based on Knowledge Management - Álvarez-Tello, Jorge (2022)
The knowledge economy and the improvement of efficiency in the dissemination and promotion of the achievements of innovation from the knowledge generated in the organization is relevant. The value chain of knowledge allows absorbing and making the most of new knowledge useful to improve competitiveness opportunities for business competitiveness. The relevant elements that evaluate the innovation of organizations based on knowledge management are delimiting through the bibliographic review in the Scopus and Google Scholar databases, using Boolean search formulas. About evaluation methods nearly to 40% work in organizational strategy, in approx. 25% include in region cluster and industry for the optimization. Hence the preponderance of topics related to knowledge optimization and innovation, decision making, value generation and knowledge supply chains. Finally, all models have limitations that must be considered, in relation to the cultural context where they are applied and the human-organizational phenomenon present. They should also consider the limitations in the use of quantitative techniques, leaving aside the richness of qualitative constructs in the analysis and strategic decision-making for a technological evolution of organizations